Real-time system support for hybrid structural simulation - Ferry, David; Bunting, Gregory; Maqhareh, Amin; Prakash, Arun; Dyke, Shirley; Aqrawal, Kunal; Gill, Chris; Chenyang Lu (2014 proceedings of the International Conference on Embedded Software (EMSOFT) : October 12-17, 2014, Jaypee Greens Golf and Spa Resort, New Delhi, India, 2014)
Real-time hybrid simulation (RTHS) is an important tool in the design and testing of civil and mechanical structures when engineers and scientists wish to understand the performance of an isolated component within the context of a larger structure. Performing full-scale physical experimentation with a large structure can be prohibitively expensive. Instead, a hybrid testing framework connects part of a physical structure within a closed loop (through sensors and actuators) to a numerical simulation of the rest of the structure. If we wish to understand the dynamic response of the combined structure, this testing must be done in real-time, which significantly restricts both the size of the simulation and the rate at which it can be conducted. Adding parallelism to the numerical simulation can enable both larger and higher frequency real-time simulations, potentially increasing both the accuracy and the control stability of the test. We present a proof-of-concept exploration of the execution of real-time hybrid simulations (an exemplar of a more general class of cyber-mechanical systems) with parallel computations. We execute large numerical simulations within tight timing constraints and provide a reasonable assurance of timeliness and usability. We detail the operation of our system, its design features, and show how parallel execution could enable qualitatively better experimentation within the discipline of structural engineering.